"Process‐based similarity" revealed by discharge‐dependent relative submergence dynamics of thousands of large bed elements. Issue 5 (29th December 2022) - Wiener, Jason; Pasternack, Gregory
Abstract: Relative submergence of macroroughness elements such as boulders and bedrock outcrops, or large bed elements (LBEs), collectively, is a primary control on hydraulics and morphodynamics in steep, coarse‐bedded rivers. However, in practice, the property is typically represented by singular, often reach‐ or cross‐section‐averaged values that mask bed‐surface heterogeneity and joint distributions of local flow depths. By coupling sub‐meter resolution two‐dimensional (2D) hydrodynamic modeling with spatially explicit mapping of LBEs from a 13.2 km segment of a boulder‐bedded mountain river, we present complete distributions of LBE relative submergences at multiple spatial scales and explore their dynamism across discharges. Through distribution fitting and statistical analysis of resultant discharge‐dependent LBE relative submergence datasets, it was confirmed that segment‐ and reach‐scale datasets exhibited similar statistical properties and were able to be drawn from the same type of distribution. Further, the rate at which statistical and parametric properties changed between discharge‐dependent datasets were statistically equivalent between spatial domains, which we term "process‐based similarity". Commonality in distribution type and the uniform between discharge–scaling relationships suggest mutual self‐organizing processes associated with the size‐frequency distribution, spatial arrangement, and submergence of LBEs were present between most domains. Abstract : Relative submergence values are calculated for thousands of spatially‐explicit river‐bed roughness elements for 5× stages ranging from baseflow to a valley‐filling flood. Results present first known documentation of distributions of relative submergence values for a natural boulder‐bedded river. Results confirm stage‐dependent changes in distributions were mainly as hypothesized, such that variances increased and central tendencies increased or remained relatively constant over tested stages. Implications of relative submergence distributions on estimating roughness coefficients, hydraulic resistance equations, and geomorphic processes are discussed.